Load Factor and Stability Analysis of PT Dharma Lautan Utama's Ro-Ro Ship at Tanjung Perak Port, Surabaya - Muhammad Akbar Maulana; Sunu Arsy Pratomo; Zihni Ihkamuddin; Capt. Sutini (Takaza Innovatix Labs Ltd., 2026)
Maritime transportation, particularly Roll-on/Roll-off (Ro-Ro) vessels, plays an important role in supporting passenger and vehicle mobility in Indonesia. Ship stability and load factor are critical aspects influencing operational safety. This study aimed to analyze the relationship between load factor and the stability of PT. Dharma Lautan Utama’s Ro-Ro vessels operating at Tanjung Perak Port, Surabaya. The study employed a descriptive quantitative design. The population consisted of operational activities of Ro-Ro vessels at PT. Dharma Lautan Utama Surabaya Branch, while the sample included operational and loading data collected from March to June 2025. Data were obtained through observation, interviews, documentation, and literature review. The research instruments included ship operational reports and stability calculation documents. Data analysis was conducted using load factor calculations and ship stability parameters, including KG, GM, GZ, and rolling period analysis. The results showed that the highest load factor in April reached 33% and was followed by the highest GM stability proportion of 31%, while the lowest load factor in March was 16% with a GM proportion of 23%. The study concludes that a higher load factor can support ship stability when cargo distribution is arranged proportionally and evenly